(untitled) (Journal of history, 2022)
This article contains questions related to the domestication of the horse and formulated a number of basic considerations about the formation of early foci of horse breeding. In connection with the study of a number of monuments of the Great Steppe Zone, the opinion has been repeatedly expressed in archaeological science about the commonality and, perhaps, the simultaneity of horse domestication in the steppe regions of South-Eastern Europe, the Volga region and Kazakhstan. According to the authors, the domestication of horses occurred on the meridian migration routes of wild animals, including horses. Of all the routes in the ancient era, the most popular was the Central One (r.Sarisu), which passed through the steppes of Saryarka. The antiquity of this route is also indicated by various mythological stories associated with some of the junction stations of this route. The authors believe that the epicenter of the coordinate system of the Eurasian steppe world was located in Saryarka, known as a political and cult center, as a cradle or father’s house (atazhurt) for many peoples. In the vast steppe expanses of Central Kazakhstan, the most complex processes in the history of nomadism were maturing and the most acutely felt violation of world harmony, at the call of which the steppe passionaries sought. Key words: Saryarka, the Great Steppe, domestication, horse, meridian route, horse breeding, steppe passionaries.